Tetraviral measles vaccination rate over the last seven years in Brazil (Research, Society and Development, 2023)
INTRODUCTION: Measles is a contagious, acute and transmissible disease that can cause complications and death. This work seeks to analyze the tetraviral vaccination rate against measles in Brazil in the last seven years, in order to evaluate the effectiveness of public immunization policies against this disease. OBJECTIVE: To analyze the tetraviral measles vaccination rate in Brazil over the last seven years. MATERIALS AND METHODS: This is a statistical, retrospective and documentary study using the DATASUS platform, which is the health information system of the Brazilian Ministry of Health, responsible for collecting, processing and making available health data in the country. RESULTS AND DISCUSSION: Measles is a serious contagious disease that can lead to death in severe cases or in patients with other diseases. Vaccination is the most effective way to prevent and ensure protection against epidemics and outbreaks. In Brazil, there are still challenges in achieving the measles immunization target, especially in vulnerable areas. CONCLUSION: disseminating accurate information and strengthening education about the importance of vaccination are crucial to ensuring the effectiveness of immunization campaigns.